Minimally Invasive management of delayed recognition iatrogenic ureteric injury - Morrow, Jessica (Ulster Med J, 2017)
INTRODUCTION: Iatrogenic ureteric injuries are a rare but serious complication of abdomino-pelvic surgery which can be associated with significant morbidity. 65-80% of ureteric trauma is only identified in the postoperative period. Current guidelines recommend stent insertion or urinary diversion via percutaneous nephrostomy. Good quality evidence on success and outcomes remains scant and the optimum treatment pathway unknown. METHODS: A retrospective review of all delayed presentation ureteric injuries treated in our unit between 2005 and 2013 was performed. Clinical, treatment and outcome data were collected in a custom proforma. RESULTS: 19 patients with 21 injured ureters met inclusion criteria. 16/19 (84.2%) injuries were sustained during gynaecological procedures with 10 (52.6%) of these during total abdominal hysterectomy. Suspected mechanisms from diagnostic studies was defined as partial transection in 9/21 (42.9%), complete transection in 3/21 (14.3%) and perforation in 1/21 (4.8%). Median time from injury to presentation was 16 days (IQR 7-25). 11/21 (52.4%) had successful stenting with a median time to stent placement of 25 days (IQR 18.5-42). Those with failed stenting had a median time to attempted stenting of 65 days (IQR 10-91.3). Those with successful stenting 3/11 (27.3%) had resolution requiring no further intervention. 6/11 (54.5%) required open reconstruction, with the remaining two patients unfit for reconstruction and managed with long term stents. With successful stenting median time to definitive surgery was 413 days (IQR 156-476). CONCLUSION: Success rates for stenting are similar to those reported in the literature (55% vs. 44-59%), but resolution rates are significantly lower (15% vs. 44-80%). Data for an endourological approach as a possible long-term solution is limited by heterogeneity, and a further well conducted multicentre prospective study is required